2021
DOI: 10.1371/journal.pone.0249222
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and associated factors of poor medication adherence among diabetic and hypertensive patients visiting public health facilities in Ethiopia during the COVID-19 pandemic

Abstract: Objective This study aims to assess the magnitude and associated factors of poor medication adherence among diabetic and hypertensive patients visiting public health facilities in Addis Ababa, Ethiopia during the COVID-19 pandemic. Methods A multi-site cross-sectional design was conducted from 1st through 30th of August 2020 at public health facilities of the study area. Adult outpatients with T2DM and hypertension visiting hospitals and health centers were included in the study. A proportion to size allocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
2
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(75 citation statements)
references
References 37 publications
6
50
2
4
Order By: Relevance
“…In various settings, improved medicine accessibility through FCPEM programs proved to help reduce patients' direct medical costs and possibly lead to increased patient participation, continuity of treatment, and better health outcomes [15,[24][25][26][27]. Furthermore, we found that patients with characteristics indicative of free medicine use in our study coincided with patients who had chronic illnesses and poor medicine use and adherence in previous studies [28][29][30]. This implies that FCPEM implementation can promote equitable access to medicines and improve the health outcomes of vulnerable populations.…”
Section: Discussionsupporting
confidence: 66%
“…In various settings, improved medicine accessibility through FCPEM programs proved to help reduce patients' direct medical costs and possibly lead to increased patient participation, continuity of treatment, and better health outcomes [15,[24][25][26][27]. Furthermore, we found that patients with characteristics indicative of free medicine use in our study coincided with patients who had chronic illnesses and poor medicine use and adherence in previous studies [28][29][30]. This implies that FCPEM implementation can promote equitable access to medicines and improve the health outcomes of vulnerable populations.…”
Section: Discussionsupporting
confidence: 66%
“…A survey in Ethiopia among diabetic and hypertensive patients reported unavailability, unaffordable or increased price of medications and interruptions in follow-up visits were common barriers to accessing chronic care units in public facilities during the pandemic. 65 Reduction in attendance for chronic conditions such as hypertensive cases is a significant finding as missing care for these chronic illnesses could lead to further complications and susceptibility to severe COVID-19, 66 and increased morbidity and mortality. The gradual decline Open access in HIV testing pre-COVID-19 might suggest reduced coverage due to policies geared towards targeted testing as opposed to blanket testing.…”
Section: Open Accessmentioning
confidence: 99%
“… 40 , 41 In addition to that, several studies state that health insurance will increase the coverage of health services and improve the community’s health status. 23 , 38 , 42 , 43 …”
Section: Discussionmentioning
confidence: 99%